General Aspects of Information Security in 5G Networks: Survey - de Castro Nunes Borges, Vitor Oriel; Lopes Rosa, Renata (INFOCOMP Journal of Computer Science, 2023)
As the deployment of 5G networks accelerates, ensuring robust security becomes paramount. This article presents a comprehensive review of security in 5G networks, aiming to analyze security applications and strategies for mitigating vulnerabilities. Through an extensive literature review, several threats and specific security vulnerabilities of 5G networks are identified as issues in corporate networks, user equipment, and applications. Furthermore, possible future security trends, vulnerability mitigations, and emerging technologies in 5G networks are explored. The article concludes by highlighting the importance of addressing security concerns in 5G networks and provides recommendations for future research in this field. Understanding the security landscape of 5G networks is crucial to ensuring the safe and reliable operation of next-generation communication infrastructure.